Decarboxylative Negishi Coupling of Redox‐Active Aliphatic Esters by Cobalt Catalysis. (4th September 2018) - Liu, Xu‐Ge; Zhou, Chu‐Jun; Lin, E.; Han, Xiang‐Lei; Zhang, Shang‐Shi; Li, Qingjiang; Wang, Honggen
Abstract: A cobalt‐catalyzed decarboxylative Negishi coupling reaction of redox‐active aliphatic esters with organozinc reagents was developed. The method enabled efficient alkyl–aryl, alkyl–alkenyl, and alkyl–alkynyl coupling reactions under mild reaction conditions with no external ligand or additive needed. The success of an in situ activation protocol and the facile synthesis of the drug molecule (±)‐preclamol highlight the synthetic potential of this method. Mechanistic studies indicated that a radical mechanism is involved. Abstract : Nützliche Verbindung : Eine Cobalt‐katalysierte decarboxylierende Negishi‐Kupplung von N ‐Hydroxyphthalimid(NHPI)‐Estern mit Organozinkreagentien ermöglicht effiziente Alkyl‐Aryl‐, Alkyl‐Alkenyl‐ und Alkyl‐Alkinyl‐Kupplungen unter milden Bedingungen und ohne externe Liganden oder Additive. Der Erfolg eines In‐situ‐Aktivierungsprotokolls und die einfache Synthese des Wirkstoffs (±)‐Preclamol unterstreichen das Potenzial der Methode.